Moral conflicts of organ retrieval : a case for constructive pluralism - Hinkley, Charles C., II (Value inquiry book series, 2020)
In this revised edition of Moral Conflicts of Organ Retrieval: A Case for Constructive Pluralism, Charles Hinkley elaborates on his moral philosophy of constructive pluralism and updates the literature on organ retrieval strategies. Hinkley challenges a deeply entrenched moral triad: 1) moral values are comparable; 2) the weighing metaphor helps us conceptualize decisions regarding conflicting values; and 3) there is a single best discoverable response to a moral decision. This book offers an alternative-cases of incomparability, a constructing or making metaphor, and multiple permissible responses to some moral questions. Constructive pluralism has important implications for organ transplantation, health, and ethics.